The effects of conditionality monitoring on educational outcomes: Evidence from Brazil's Bolsa Família programme - Luis Henrique Paiva; Fabio Veras Soares; Flavio Cireno; Iara Azevedo Vitelli Viana; Ana Clara Duran (Institute for Applied Economic Research (ipea), 2016)
Conditional cash transfer programmes have been increasingly adopted by several low and middle-income countries. Despite this overall acceptance, conditionalities remain under scrutiny regarding their possible independent effects on educational and health indicators. This paper is an ecological study of conditionalities in Brazil's Bolsa Família programme. As programme coverage (taken as a proxy of cash transfers) and monitoring and enforcement of the educational conditionalities (proxy of conditionalities) are not correlated at the municipal level, this study fits a number of different ordinary least square (OLS) and growth-curve models to explain variations in drop-out rates and school progression in basic education in public schools across municipalities. After controlling for potential confounding factors, we do not find a positive association between Bolsa Famìlia coverage and drop-out and progression rates (in either OLS or growth-curve models). On the other hand, monitoring of school attendance is negatively associated with drop-out rates and positively associated with school progression (in the OLS model and in the initial status of the growth-curve model). The association between attendance monitoring and the rate of change of the educational indicators studied is not what was expected, however - suggesting that its positive effect on educational indicators (found in the initial status) tends to be less significant for the rate of change of the variables of interest.
Keywords: I28; I38; 330; conditional cash transfers; educational outcomes; Bolsa Familia; growth-curve models